Influence of farmer organizations as a market information system on market access and income of smallholder vegetable farmers in Babati District, Tanzania - Aku, A.O. (Egerton University, 2017)
Vegetable production is of great importance in terms of nutrition improvement, income generation and food security. Africa Research in Sustainable Intensification for the Next Generation (Africa RISNG) action research project actively integrates vegetable farming and marketing practices in order to reduce the vulnerability of indigenous populations of Babati district located in the Manyara region of Tanzania. In Tanzania smallholder vegetable famers receive asymmetrical and incomplete market information which is costly. Mobilizing farmers into groups so as to access viable market information while enhancing their bargaining power is one way to overcome this challenge. However, the extent to which this has been achieved has not yet been evaluated. This study sought to evaluate the influence of farmer organizations towards improving smallholder income in Babati. Objectives of the study were: to determine types of market information accessed by smallholder vegetable farmers through farmer organizations, determine factors influencing information seeking behaviour of vegetable farmers and determine effect of access to market provided by farmer organizations on smallholder vegetable farmer’s income. The target population was smallholder farmers who grow vegetables within maize based farming systems. Multi-stage sampling technique was employed where by 250 smallholders’ vegetable farmers were interviewed using structured questionnaire. The results showed that the type of market (29%) is the most type of market information accessed by vegetable farmer through farmer organization. From the Poisson model the results show that distance to the market information source point has a negative influence on farmer’s information seeking behaviour. In contrast, gender, education, income and group membership had a significant positive relationship with farmers’ information seeking behaviour. In estimating the effect of access to market provided by farmer organizations on smallholder vegetable farmer’s income, Propensity Score Matching (PSM) was used. The results indicate that farmers who had access to the market provided by farmer organization have more income (501691.413 TZS) than non member (405471.429 TZS). From the results, it is recommended that an enabling policy environment that establishes and strengthens farmer organizations be supported. This will assist in transforming smallholder farming as viable business ventures through increased productivity and increased household incomes while reducing rural poverty.